Scripts of Blackness: Early Modern Performance Culture and the Making of Race by Noémie Ndiaye (review). - Vipperman-Cohen, Mel (Journal for Early Modern Cultural Studies)
The article focuses on Noémie Ndiaye's book, *Scripts of Blackness: Early Modern Performance Culture and the Making of Race*, which examines the construction of racial identities through performance in early modern theater across Spanish, French, and English contexts. Ndiaye analyzes how white actors' impersonations of Afro-diasporic individuals contributed to the creation of racial scripts that perpetuated stereotypes of blackness associated with animalism and subservience. The book is organized around three main themes: cosmetic blackness, acoustic blackness, and kinetic blackness, each revealing the complexities of racial representation and the colonial implications of these performances. Ndiaye's work challenges the traditional focus on Anglophone literature, offering a broader understanding of race-making practices in early modern performance culture.